2023
DOI: 10.1111/gcb.16877
|View full text |Cite
|
Sign up to set email alerts
|

Climate change drives loss of bacterial gut mutualists at the expense of host survival in wild meerkats

Abstract: Climate change and climate‐driven increases in infectious disease threaten wildlife populations globally. Gut microbial responses are predicted to either buffer or exacerbate the negative impacts of these twin pressures on host populations. However, examples that document how gut microbial communities respond to long‐term shifts in climate and associated disease risk, and the consequences for host survival, are rare. Over the past two decades, wild meerkats inhabiting the Kalahari have experienced rapidly risi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Experimental studies using both long read sequencing and shotgun metagenomics are needed to improve taxonomic resolution (in this study many ASVs could only be assigned to genus/family level) and quantify functional profiles of the bank vole gut microbiota. This information, together with long-term survival and fitness data, can help to further elucidate the role of the gut microbes in facilitating host adaptation to a change in the environment through potential differences in disease susceptibility [ 71 , 72 ], energy uptake from food [ 73 ], detoxification of plant compounds [ 74 ], stress physiology [ 55 ] and/or survival rate [ 75 , 76 ], as reported in various animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies using both long read sequencing and shotgun metagenomics are needed to improve taxonomic resolution (in this study many ASVs could only be assigned to genus/family level) and quantify functional profiles of the bank vole gut microbiota. This information, together with long-term survival and fitness data, can help to further elucidate the role of the gut microbes in facilitating host adaptation to a change in the environment through potential differences in disease susceptibility [ 71 , 72 ], energy uptake from food [ 73 ], detoxification of plant compounds [ 74 ], stress physiology [ 55 ] and/or survival rate [ 75 , 76 ], as reported in various animal species.…”
Section: Discussionmentioning
confidence: 99%
“…The results however, differ from a number of other studies ( Jha et al, 2011 ; Pokhrel & Maharjan, 2014 ; Sapkota, 2020 ). Climate change is altering the intestinal microbiome of wildlife, and these modifications may intensify the adverse effects of climate change ( Risely et al, 2023 ). It is suggested that Oesophagostomum spp., Ascaris spp., and Trichuris spp.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the environmental variables on each predator species’ presence/absence was analysed with a generalised linear latent variable model (GLLVM; ‘gllvm’ v1.4.1 R package 108 ). GLLVMs can be powerful tools that allow integration of multiple predictor variables into a single model, while accounting for differences in the response of multiple species 109 . Due to the binary response (presence/absence), the model was fitted as a binomial distribution, while the predictor variables were the principal components retained from the PCA performed on the environmental data.…”
Section: Methodsmentioning
confidence: 99%